Penerapan Pendekatan PAKEM dengan Monopoly Game Untuk Meningkatkan Hasil Belajar Belajar Siswa SMP - Mayanty, Sri (Universitas Halu Oleo, 2021)
This research is motivated by low student learning activities that have an impact on learning outcomes. In order for students learning activities to increase, one of which requires an appropriate learning approach and media, therefore this study uses the PAKEM approach with monopoly games. This study aims to determine the increase in student learning outcomes after the PAKEM approach with monopoly games is apllied. The research method used was pre-experimental design. The results of data processing cognitive learning outcomes obtained a normalized average gain of 0,47 in the moderate category. The profile of learning outcomes in the affective domain, in the aspect of listening to explanations and activeness, is in the good category. While for aspects of fluency in communicating, responsibility and cooperation are in the sufficient category. The profile of student learning outcomes in the psychomotor domain, the aspect of using measuring instruments is in the sufficient category while the aspect of conducting investigations is in the good category. However, is this study there are still things that need to be improved, namely providing reinforcement in learning and providing more space for students to build communication,